Optične metapovršine - Korenjak, Zala (Matrika, 2021)
Optical metasurfaces are ultra thin metamaterials consisting of one layer of spatially arranged nanoantennas exhibiting special optical properties. The article first describes plasmonic type of metasurfaces and fundamental principles of their operation. The second part of the article is dedicated to applications of optical metasurfaces as optical elements for phase, polarization and amplitude control of light. Finally, we discuss some possible mechanisms of active control of metasurfaces and change of their optical properties.
Keywords: optical metasurfaces; optical properties; optične lastnosti; optične metapovršine; ultra tanki metamateriali; ultra thin metamaterials